Genetics Reveal Long-Distance Virus Transmission Links in Pacific Salmon - Breyta, Rachel B.; Batts, William N.; Kurath, Gael (Animals (Basel), 2022)
In the coastal region of Washington State, a major pathogen emergence event occurred between 2007 and 2011 in which steelhead trout (Oncorhynchus mykiss) experienced a high incidence of infection and disease outbreaks due to the rhabdovirus infectious hematopoietic necrosis virus (IHNV). Genetic typing showed that the introduced viruses were in the steelhead-specific MD subgroup of IHNV and indicated the most likely source was a virus from the nearby Columbia River Basin. In the current study, full-length viral glycoprotein (G) gene sequences were determined for 55 IHNV isolates from both coastal and Columbia fish populations to identify specific source populations and infer mechanisms of transmission to coastal steelhead. We identified three transmission links based on exact fullG genotype matches between Columbia and coastal fish. In all cases, the likely source population was infected juvenile fish, and sink populations were adult fish returning to coastal rivers to spawn. The time intervals between detection in source and sink populations varied from 6 months to nearly 4 years, suggesting different transmission pathways. Surprisingly, distances between source and sink populations varied between 140 and 1000 km. These results confirm repeated introductions of virus from Columbia River Basin fish as the cause of emergence of MD virus on the Washington coast from 2007 to 2011.